Vogt-Koyanagi-Harada Disease: A Case Series in a Tertiary Eye Center - Pranav Shrestha; Sadhana Sharma; Ranju Kharel (Case Reports in Ophthalmological Medicine)
Purpose. To study the clinical spectrum of Vogt-Koyanagi-Harada (VKH) disease in a tertiary eye center in Nepal. Methods. Baseline demographic details and clinical features of six patients diagnosed as VKH in a tertiary eye center were retrospectively reviewed. Examinations included best corrected visual acuity, intraocular pressure, and slit lamp examination of anterior and posterior segments. Baseline blood investigations, chest X-ray, fundus photography, and fundus fluorescent angiography (FFA) were performed on all the patients. Results. The mean age at presentation was 46±8.43 years with female predominance (83.3%). The disease was complete in 16.7%, incomplete in 16.7%, and probable in 66.7% of the patients. Most cases presented in acute uveitis stage (66.7%). The most common finding in acute cases was serous retinal detachment (66.7%), followed by disc edema (58.3%), whereas in chronic cases, depigmented fundus was the most common. All cases had bilateral presentation. Conclusion. VKH is an important cause of bilateral loss of vision and has a good visual prognosis if aggressive treatment is initiated during the early stages.